Surgical Techniques to Prevent Nipple-Areola Complex Malposition in Two-Stage Implant-Based Breast Reconstruction - Komiya, Takako; Ojima, Yosuke; Ishikawa, Takashi; Matsumura, Hajime (Archives of Plastic Surgery, 2022)
Background Appropriate position of the nipple-areolar complex (NAC) is crucial following nipple-sparing mastectomy (NSM). The prevention of NAC malposition in two-stage implant-based breast reconstruction has not been well described, and the efficacy of the techniques has not been evaluated. This study aimed to evaluate the efficacy of our technique to prevent NAC malposition in patients who underwent implant-based breast reconstruction after NSM.Methods Patients who underwent two-stage implant-based breast reconstruction with NSM between January 2012 and December 2019 were included. We used a surgical technique to fix the NAC to the rigid base, assuming a pocket-like appearance, with pectoralis major muscle and lateral adipofascial flap at the time of tissue expander (TE) insertion. Patients were classified into two groups based on the performance of the technique for the prevention of NAC malposition.Results In 35 patients who underwent implant-based breast reconstruction after NSM, the clavicle-to-nipple distance ratio was 96.0 ± 5.0% in those who underwent NAC fixation and 86.1 ± 11.5% in those who did not undergo NAC fixation.Conclusions Using our technique, NAC malposition could be prevented in two-stage implant-based breast reconstruction. NAC fixation during TE insertion was found to be extremely effective. This procedure successfully prevented NAC malposition without the formation of extra scars.
Keywords: nipple-sparing mastectomy; nipple-areolar complex malposition; two-stage implant-based breast reconstruction; breast reconstruction